Evaluation of Painful Shoulder with High Frequency Sonography and their Comparison with the Clinical Diagnosis made by Physical Examination (Nepalese Journal of Radiology, 2013)
Purpose: The purpose of this study is to compare clinical diagnosis made by physical examination with high frequency ultrasonographic findings and also to correlate ultrasonographic findings of painful shoulders of cases with asymptomatic shoulders of control subjects. The most common clinical diagnosis was supraspinatus lesion (38) followed by bicep tendon lesion (14) .Rotator cuff was the most common structure to show abnormality (critical zone of avascularity) with supraspinatus being the most commonly involved tendon in our study. Non-invasiveness, easy availability along with its cost effectiveness justify role of high frequency ultrasound in the assessment of painful shoulder. Nepalese Journal of Radiology; Vol. 2; Issue 2; July-Dec. 2012; 43-50 DOI: http://dx.doi.org/10.3126/njr.v2i2.7684